Management’s Commitment, Education and Ethics on Organisational Entrepreneurship: The Case of South African Non-Profit Organisations - Pamacheche, Rukudzo; Chinomona, Richard; Chuchu, Tinashe (Journal of Economics and Behavioral Studies, 2016)
The objectives of the study were to explore the management characteristics that are related to organisational entrepreneurship in not-for-profit organisations (NPOs) in Gauteng, South Africa as well as the relationship between organisational entrepreneurship and the organisational performance. The methodology involved a quantitative approach of collecting and analysing research data. A field study was conducted in Johannesburg, South Africa whereby research data were collected from 257 NPO managers from voluntary organizations. Using the SPSS 22 and the AMOS 22 software program, Structural Equation Modeling (SEM) was performed to analyze the research data. The study noted implications for NPO management teams, including the renovation of business model structures to incorporate continuous learning and constructive risk-taking in order to take advantage of the performance benefits derived from organisational entrepreneurship. The study also recommends further research into potential citizenship bodies for NPO management teams to foster commitment to their occupation in the non-profit sector. The research makes a significant contribution by providing a framework in which management’s commitment to NPOs can be measured and analysed.